The module mir156/spl affects bixin biosynthesis pathway in annatto (Bixa orellana L.) - Machado, Kleiton Lima de Godoy (2022)
Annatto [Bixa orellana L. (Bixaceae)] is a woody plant species that can reach up to 6 meters in height, with a fast growth pattern. Annatto produces a main apocaterotenoid namely bixin, a unique natural dye. This compound is highly used in the textile, pharmaceutical and food industries, among others, making annatto an important crop in both ecological and economic aspects. Despite its relevance, there are several gaps for the understanding of its developmental processes. Perhaps one of the most interesting is the role of miR156/SPL module in its physiology. This microRNA is responsible for integrating plant physiology development through modulation of SPL transcription factors that modulate leaf morphology and anatomy, among other characteristics that may be linked to secondary metabolites production. In this particular, the miR156/SPL module regulates the biosynthesis of sesquiterpenes, flavonoids, anthocyanins, and carotenoids in higher plants. In this context, B. orellana is a promising woody species with an expressive secondary metabolism activity. Therefore, we aimed to assess phenotypic changes, plant phenology, hormonal profile, secondary metabolism, expression of developmental-linked genes, and proteome portray in overexpressing miR156 lines of B. orellana plants (OE::156). We observed new patterns in plant architecture and leaf blade features. In addition, higher IAA and ABA levels were found in OE::156 plants compared to non-transformed plants (Nt). Moreover, OE::156 plants have lower bixin content than Nt. Furthermore, CCD4 showed lower expression in contrast to higher CCD1 transcriptional levels. Besides that, the proteome showed ZEP upaccumulation in OE::156 plants, which indicates that carbons are being translocated from bixin to ABA production. Further studies are suggested to understand the role of specific secondary metabolites regulation by miR156/SPL module. Keywords: microRNA. SPL proteins. Plant development. Phase change. Proteomics.